Bone marrow adiposity and multiple myeloma - Morris, E; Edwards, C (Elsevier, 2018)
Multiple Myeloma (MM) is an incurable haematological malignancy and is the second most common blood cancer in adults; it is caused by the clonal expansion of abnormal plasma cells within the bone marrow and characterized by osteolytic bone lesions, bone pain, renal disease, and immunodeficiency. MM cells infiltrate the bone marrow where they hijack the microenvironment to sustain growth and survival. The contribution to this process by resident bone cells is well defined. However, the role of bone marrow adipocytes is less clear. As one of the most abundant cell types in the bone marrow these cells are surprisingly understudied. However, in the last few decades they have been recognised as having endocrine function. Adipocytes are metabolically active cells that secrete adipokines, growth factors, and inflammatory mediators, they influence the behaviour and function of neighbouring cells; and have the potential to dysregulate normal bone homeostasis. This review discusses how adipocytes contribute to the metastatic niche in multiple myeloma and cancers that metastasise to the bone and how these new discoveries may contribute to further understanding the mechanisms driving the devastating bone disease associated with MM.